2018
DOI: 10.18502/cmm.4.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal effects of ethanolic and aqueous extracts of Vitex agnus-castus against vaginal isolates of Candida albicans

Abstract: Background and Purpose:Vulvovaginal candidiasis is one of the most common infections in female genital organs, which is caused by Candida species. Candida albicans is the causative agent of more than 80% of infections, and the role of non-Candida strains in the disease etiology is less prominent. The expansion of Azoles resistance among C. albicans strains is considered an important medical problem. According to previous studies, Vitex agnus-castus (vitex) has some antimicrobial effects. We aimed to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 8 publications
5
9
0
Order By: Relevance
“…Several of these secondary metabolites belong to important chemical groups such as polyphenols, fatty acids, terpenes, terpenoid, steroids, aldehydes, alcohol, and esters. These results are in agreement with a previous study of Keikha et al (2018), which stated that the VA-C extract was rich in chemical compounds, and the alcoholic extract contained 36 chemical compounds that belong to different chemical groups. Our results showed that the majority of compounds were 4,5-Dichloro-1,3-dioxolan-2-one in both ethanol and methanol, 1H-Indene, 2,3-dihydro-1,1,2,3,3pentamethyl in ethanol, Isobutyl 4-hydroxybenzoate in methanol, and Benzoic acid and 4-hydroxy-in water.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Several of these secondary metabolites belong to important chemical groups such as polyphenols, fatty acids, terpenes, terpenoid, steroids, aldehydes, alcohol, and esters. These results are in agreement with a previous study of Keikha et al (2018), which stated that the VA-C extract was rich in chemical compounds, and the alcoholic extract contained 36 chemical compounds that belong to different chemical groups. Our results showed that the majority of compounds were 4,5-Dichloro-1,3-dioxolan-2-one in both ethanol and methanol, 1H-Indene, 2,3-dihydro-1,1,2,3,3pentamethyl in ethanol, Isobutyl 4-hydroxybenzoate in methanol, and Benzoic acid and 4-hydroxy-in water.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, we showed that the inhibitory capacity of the solvents varied significantly in descending order of ethanol, then water, then methanol. These results are in line with a recent study conducted by Keikha et al (2018) who found that VA-C ethanol leaf extract has the highest inhibiting effect against C. albicans isolates than water extract. Our results showed a similarity in the inhibitory effect of all extracts with nystatin (10 mcg) as a positive control against C. albicans, where the inhibitory effect for the positive control was higher than all extracts against C. tropicalis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Vitex agnus-castus L. leaf essential oil eliminated the cariogenic bacteria Streptococcus mutans (MIC = 15.6 µg/mL) [71]. In another study, alcoholic and aqueous extracts had an antifungal effect on C. albicans isolated from clinical vaginal infections [72]. Vitex agnus-castus L. seed essential oil showed antifungal activity against Candida species (IC 50 = 1.072 mg/mL) and also antioxidant potential [73].…”
Section: Health-promoting Activities Of Vitex Agnus-castus L In Vitromentioning
confidence: 95%